On the Fraught Subject of Value. - PIERCE, WILLIAM (AGNI (1046-218X), 2022)
The article offers information about the writing skills and subjects. It discusses about the abstract framework, atmosphere, exploration, imaginative writing, and certain details of technique. It mentions the collection Black Paper, writers Teju Cole about the importance of the Italian painter Caravaggio.